Change in Symptoms and Mucosal Findings after Proton Pump Inhibitor in Patients with Laryngopharyngeal Reflux - Min Woo Park; Sin Jae Kang; Jee Hye Wee (International Archives of Otorhinolaryngology)
Introduction Although there are several reports of endoscopic findings of the larynx and esophagus in laryngopharyngeal reflux (LPR) patients, little is known about the correlation between change in symptoms and laryngeal and esophageal mucosal findings after proton pump inhibitor (PPI) treatment.